Economic Order Quantity (EOQ) Analysis of Sweet Soy Sauce Inventory Control from Sorghum: A Comparative Study - Muhamad Hairul Mu'minin; Zulmaneri Manir (Winaya Inspirasi Nusantara Foundation, 2025)
Background of the problem: Inventory of sweet soy sauce raw materials from sorghum continues to increase every year. This spike is influenced by the increasing frequency of ordering sweet soy sauce products from consumers. Purpose: To analyze the difference between the inventory costs incurred by the company using the Economic Order Quantity (EOQ) method. Method: Case study; the data are the operations managers' interviews. Data analysis was performed using the EOQ method. Result: The cost savings for inventory costs in 2022 were 37% for premium sweet soy sauce and 60.69% for ordinary soy sauce; in 2023 it could save 40.50% for premium sweet soy sauce and 59.40% for ordinary sweet soy sauce. And in 2024, it can save inventory control of premium sweet soy sauce by 67.04% and ordinary sweet soy sauce by 74.70%, according to the EOQ method. The EOQ method is considered more efficient in determining the cost of raw materials for a company's expenditure. Implication: The findings also have broad relevance and can be applied to other companies in the food and beverage industry sector that face similar challenges in managing raw materials.